2016
DOI: 10.1590/1414-431x20165178
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production and organic solvent stability of a protease fromBrevibacillus laterosporus strain PAP04

Abstract: A bacterial strain (PAP04) isolated from cattle farm soil was shown to produce an extracellular, solvent-stable protease. Sequence analysis using 16S rRNA showed that this strain was highly homologous (99%) to Brevibacillus laterosporus. Growth conditions that optimize protease production in this strain were determined as maltose (carbon source), skim milk (nitrogen source), pH 7.0, 40°C temperature, and 48 h incubation. Overall, conditions were optimized to yield a 5.91-fold higher production of protease comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Also, it goes up for solving problems by producing of producing nontraditional materials as antimicrobial agents [4][5][6], nanobiosynthesized metals like silver, copper and zinc [7,8] and biotechnological agents as bioactive materials [9][10][11][12]. Extremophile microorganisms have various adaptation mechanisms enabling them to thrive and produce secondary metabolites under harsh conditions [13][14][15]. Extremophiles are ≤ H y [6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it goes up for solving problems by producing of producing nontraditional materials as antimicrobial agents [4][5][6], nanobiosynthesized metals like silver, copper and zinc [7,8] and biotechnological agents as bioactive materials [9][10][11][12]. Extremophile microorganisms have various adaptation mechanisms enabling them to thrive and produce secondary metabolites under harsh conditions [13][14][15]. Extremophiles are ≤ H y [6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Extremophile microorganisms have various adaptation mechanisms enabling them to thrive and produce secondary metabolites under harsh conditions [13][14][15]. Extremophiles are ≤ H y [6][7][8][9][10][11][12][13][14][15][16][17][18]. Extremophiles isolates from different habitats include soil, compost, manure [19], geothermal areas [20], sewage sludge or municipal solid waste [21], oil wells [22] and thermally treated foods [23].…”
Section: Introductionmentioning
confidence: 99%
“…Skim milk in the media, for instance, was the most effective nitrogen source to increase protease production. In addition, there were several other sources of nitrogen, such as casein and gelatin (Anbu, 2016). Several studies that identified proteolytic bacteria from several sources aimed at the application of these microbes in scientific development activities and biotechnology (Ebrahempour and Ashraf, 2015).…”
Section: Figure2mentioning
confidence: 99%
“…Microbial proteases act like virulence factors and are known to damage the defense proteins of the host organism. Commonly used microorganisms for protease production include Streptococcus sp., Bacillus sp., Streptobacillus sp., P. aeruginosa, and E. coli [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%